Development of interactive e-books in tissue culture learning for class xi science - Mellisa Mellisa; Delma Saputri (Biosfer: Jurnal Pendidikan Biologi, 2023)
The learning media used in schools is in the form of books. In addition, the media used by schools contains material that is not yet specific and not yet interactive, so it is necessary to develop media that suits needs, such as interactive e-books. This study aims to produce an interactive e-book learning media on the tissue culture sub-material on the structure and function of tissues in plants that are valid. This development research uses the ADDIE development model whose implementation reaches the third stage, namely Analysis, Design, and Development. This interactive e-book was created using the Flip PDF Corporate Edition application. The sampling technique used in this research is random sampling. The sample used in the study was 45 students of class XI IPA SMA. The data collection instruments used were validation sheets and validated student response questionnaires. Data collection was carried out using student and teacher response questionnaires. Product validation uses validation sheets carried out by material, media, and learning experts. Data were analyzed using the analytical technique of the scale method with a modified Likert scale. The average product validation test results obtained a percentage of 91.62% with a very valid interpretation. The developed learning media also received good responses from students in three schools with an average percentage of 79.75% with good interpretation. So it can be concluded that the developed interactive e-book learning media is very valid for use in learning. Further research is needed to develop and test the effectiveness of media in the learning process